LISTA RECENZENTÓW ROCZNIKA 2015 - SP, Redakcja (Studia Psychologica: Theoria et praxis, 2016)
Agata Błachnio Jan Cieciuch Przemysław Cynkier Zbigniew B. Gaś Stanisław Głaz Oleg Grobaniuk Lidia Grzesiuk Krzysztof Henne Aleksandra Jasielska Aleksandra Jaworowska Zygfryd Juczyński Katarzyna A. Knopp Dariusz Krok Maria Ledzińska Beatrice Ligorio Andrzej Margasiński Anna Matczak Jolanta Miluska Nina Ogińska-Bulik Andrzej Pankalla Kazimierz Pospiszyl Aneta Przepiórka Patrycja Rudnicka Maria Ryś Piotr Socha Małgorzata Starzomska Sławomir Ślaski Jacek Śliwak Beata Zarzycka Bogdan Zawadzki